Promoting Teen Mothers' Mental Health. Issue 2 (March 2016) - Freed, Patricia; SmithBattle, Lee
Abstract : Abstract: In this second article in a two-part series, we call for the integration of strengths-based and trauma-informed care into services for teen mothers. Nurses working with teen mothers in health clinics, schools and home visiting programs can play a pivotal role in promoting their mental health. Many teen mothers have high levels of psychological distress and histories of adverse experiences that cannot be ignored, and cannot solely be addressed by referral to mental health services. Nurses must be prepared to assess for trauma and be open to listening to teen mothers' experiences. Principles of strengths-based and trauma-informed care are complementary and can be integrated in clinical services so that teen mothers' distress is addressed and their strengths and aspirations are supported. Potential screening tools, interviewing skills and basic strategies to alleviate teen mothers' distress are discussed. Abstract : Teen mothers may have experienced adverse childhood experiences that were distressing and traumatic. These events can have a negative influence on their pregnancy and parenting. Trauma-informed care and strengths-based care can be helpful in supporting teen mothers.